2013
DOI: 10.1016/j.ypmed.2013.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient and excessive amounts of sleep increase the risk of premature death from cardiovascular and other diseases: The Multiethnic Cohort Study

Abstract: Objective To explore an independent association between self-reported sleep duration and cause-specific mortality. Methods Data were obtained from the Multiethnic Cohort Study conducted in Los Angeles and Hawaii. Results Among 61,936 men and 73,749 women with no history of cancer, heart attack or stroke, 19,335 deaths occurred during an average 12.9 year follow-up. Shorter (≤5 h/day) and longer (≥9 h/day) sleepers of both sexes (vs. 7 h/day) had an increased risk of all-cause and cardiovascular disease (CV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
87
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 51 publications
8
87
1
1
Order By: Relevance
“…A total of 74 studies met the inclusion criteria; the process of study selection is shown in Figure 1 8, 9, 11, 12, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89,...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 74 studies met the inclusion criteria; the process of study selection is shown in Figure 1 8, 9, 11, 12, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89,...…”
Section: Resultsmentioning
confidence: 99%
“…For the meta‐analysis, there were 7 studies37, 47, 49, 51, 61, 75, 78 (Data S11) and 15 studies**** (Data S12) for CHD mortality and CHD, respectively. Although there were fewer studies, a similar J‐shaped pattern was observed where there was greater risk of CHD mortality and events with incremental deviation from the reference 7 to 8 hours of self‐reported sleep (a modest increase for 6 hours and greater increase for ≤5 hours; Data S10).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study of US adults (N = 135,685) followed for almost 13 years, shorter (≤5 h/day) and longer (≥9 h/day) sleepers of both sexes had an increased risk (vs. 7 h/day) of all-cause and CVD mortality (Kim et al, 2013). In a prospective study of Dutch adults (N = 20,432) followed for 10-15 years, those reporting short sleep (≤6 h) at baseline were at 15 % greater risk of developing CVD and 23 % greater risk of coronary heart disease (CHD) relative to those sleeping 7 h (Hoevenaar-Blom et al, 2011).…”
Section: Introductionmentioning
confidence: 99%